2017
DOI: 10.1007/s12639-017-0881-y
|View full text |Cite
|
Sign up to set email alerts
|

A study on prevalence and factors associated with ectoparasitism in goats of two agro-climatic regions in India

Abstract: The present study was aimed to evaluate the factors associated with prevalence of various ectoparasites among goats during winter season in two different agro-climatic regions of India. A total of 320 goats (Uttarakhand-208; Uttar Pradesh-112) were screened and evaluated for ectoparasitism and associated factors. The occurrence of ectoparasitism in goats was studied in relation with age, sex, breed, housing, agro-climatic region and system of rearing. Prevalence of ectoparasitism among goats of lower Shivalik … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…In different parts of South Asia, the prevalence study of ectoparasitism was observed among goats (Sarkar et al, 2010 andIqbal et al, 2014). In India, the prevalence and factors associated with ectoparasitism were evaluated in goats of two different agro-climatic regions (Ajith et al, 2017).…”
Section: Page159mentioning
confidence: 99%
“…In different parts of South Asia, the prevalence study of ectoparasitism was observed among goats (Sarkar et al, 2010 andIqbal et al, 2014). In India, the prevalence and factors associated with ectoparasitism were evaluated in goats of two different agro-climatic regions (Ajith et al, 2017).…”
Section: Page159mentioning
confidence: 99%
“…Caprine pediculosis is considered as a major ectoparasitic condition commonly seen among goats reared under an extensive grazing system, mainly during the winter season (Iqbal et al 2014). It is reported from almost all parts of the world, especially from the Dehradun valleys of the subtropical Himalayas, tropical Asia and parts of Africa (Adesh et al 1994; Ajith et al 2017a). Based on their feeding habits, aetiological agents of caprine pediculosis can be classified into two subgroups: sucking lice (suborder: Anoplura), which includes blood feeders such as Linognathus stenopsis and L. africanus, and chewing or biting lice (suborder: Mallophaga), which includes non-blood feeders such as Bovicola (Damalinia) caprae and B. limbata (Taylor, Coop & Wall 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their feeding habits, aetiological agents of caprine pediculosis can be classified into two subgroups: sucking lice (suborder: Anoplura), which includes blood feeders such as Linognathus stenopsis and L. africanus, and chewing or biting lice (suborder: Mallophaga), which includes non-blood feeders such as Bovicola (Damalinia) caprae and B. limbata (Taylor, Coop & Wall 2007). The common chewing lice found among goats in India were B. caprae (Ajith et al 2017a; Giri, Kashyap & Dewangan 2013). These are small (approximate size: 1 mm – 2 mm) permanently parasitic insects of the Phthiraptera family, seen close to the skin, and complete their whole life cycle on the host body surface and transmission occurs only by direct physical contact (Smith & Sherman 2009; Taylor et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Mahatma Gandhi described goats as “Poor man's cow”; because meat and milk of goats serve as the major source of high quality animal protein for the rural children in developing countries like India . Ectoparasitism imparts significant production losses in goat farming and the most common ectoparasites found among Indian goats are lice, fleas, mites and ticks . Flea allergy dermatitis (FAD) or flea bite hypersensitivity is a dermatologic condition observed in goats more prevalently in summer months during which optimal climatic conditions for flea development prevail .…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Ectoparasitism imparts significant production losses in goat farming and the most common ectoparasites found among Indian goats are lice, fleas, mites and ticks. [3][4][5] Flea allergy dermatitis (FAD) or flea bite hypersensitivity is a dermatologic condition observed in goats more prevalently in summer months during which optimal climatic conditions for flea development prevail. 6 Fleas are small flightless haematophagous insects that form the order Siphonaptera, and the most common siphonapteran responsible for caprine FAD is Ctenocephalides felis.…”
Section: Introductionmentioning
confidence: 99%